Pelatihan media pembelajaran digital berbasis audio visual bagi guru PJOK di Kabupaten Probolinggo - Wahyu Nofiyan Hadi; Hartanto; Amrinatul Husna; Fiqih Fendi (Jurnal Dedikasi Masyarakat, 2024)
This community service initiative aims to enhance the understanding and skills of Physical Education, Sports, and Health (PJOK) teachers in Probolinggo Regency in developing and utilizing digital audio-visual learning media. The training was designed to address challenges related to low digital literacy among PJOK teachers and limited integration of technology in the learning process. The program was implemented in three phases: socialization, training, and evaluation, using lectures, interactive discussions, and hands-on simulations. A total of 50 PJOK teachers actively participated in both online and offline sessions. The results showed a significant increase in participants’ enthusiasm, conceptual understanding, and technical competence in creating engaging and relevant digital learning materials. This activity successfully encouraged teachers to become more adaptive to technological advancements in education, thereby improving the quality of PJOK instruction in a more innovative and effective manner.